Radiogenic heat production of S-type and I-type granite rocks in Bangka Island, Indonesia: DOI: 10.48129/kjs.15423 - Siregar, Rahmat Nawi; Kurnia Setiawan Widana; Sismanto (Kuwait Journal of Science, 2022)
Radiogenic heat production (RHP) has been investigated from widely types of rocks based on regional setting and metamorphism grade. In this study, we analyze the abundance of heat producing elements (U, Th, K) and Radiogenic Heat Production (RHP) on I-type and S-type granite rocks in Bangka Island, one of the main provinces in Tin Belt Island. The average U, Th and K concentrations for both S-type and I-types granite are 10.27 ppm, 79.6 ppm, 3.1% and 87.79 ppm, 99.2 ppm and 1.93 % respectively. The highest concentration of U (681.22 ppm) and Th (99.2 ppm) are found in Pangkal Pinang and K (3.79%) in West Bangka. We analyze that RHP average for I-type granite is higher with 27.87 (N=17, range from 12.97 to 550.28) than S-type with 8.43 (N=11, range from 4.93 to 12.64). The Th/U ratio shows an exponential correlation with RHP and classifies S-type granite tectonic discriminant as continental collision and I-type granite as continental arc.